Presentations due to acute toxicity of psychoactive substances in an urban emergency department in Switzerland: a case series. Issue 1 (December 2016) - Liakoni, Evangelia; Dolder, Patrick; Rentsch, Katharina; Liechti, Matthias
Abstract Background Although the recreational use of psychoactive substances is common there is only limited systematic collection of data on acute drug toxicity or hospital presentations, in particular regarding novel psychoactive substances (NPS) that have emerged on the illicit market in the last years. Methods We included all cases presenting at the emergency department (ED) of the University Hospital of Basel, Switzerland, between October 2014 and September 2015 with acute toxicity due to self-reported recreational drug use or with symptoms/signs consistent with acute toxicity. Intoxications were confirmed using immunoassays and LC-MS/MS, detecting also novel psychoactive substances. Results Among the 50'624 attendances at the ED, 210 were directly related to acute toxicity of recreational drugs. The mean patient age was 33 years and 73 % were male. Analytical drug confirmation was available in 136 cases. Most presentations were reportedly related to cocaine (33 %), cannabis (32 %), and heroin (14 %). The most commonly analytically detected substances were cannabis (33 %), cocaine (27 %), and opioids excluding methadone (19 %). There were only two NPS cases; a severe intoxication with paramethoxymethamphetamine (PMMA) in combination with other substances and an intoxication of minor severity with 2, 5-dimethoxy-4-propylphenethylamine (2C-P). The most frequent symptoms were tachycardia (28 %), anxiety (23 %), nausea or vomiting (18 %), and agitation (17 %). Severe complications included two fatalities, two acute myocardial infarctions, seizures (13 cases), and psychosis (six cases). Most patients (76 %) were discharged home, 10 % were admitted to intensive care, and 2 % were referred to psychiatric care. Conclusion Most medical problems related to illicit drugs concerned cocaine and cannabis and mainly included sympathomimetic toxicity and/or psychiatric disorders confirming data from the prior year. Importantly, despite the dramatic increase in various NPS being detected in the last years, these substances were infrequently associated with ED presentations compared with classic recreational drugs.